2022
DOI: 10.3390/en15176239
|View full text |Cite
|
Sign up to set email alerts
|

Iraq Oil Industry Infrastructure Development in the Conditions of the Global Economy Turbulence

Abstract: The resource orientation of the Iraqi economy implies the development of a competitive advantage of the oil industry through the industry’s infrastructure development. The authors' assumption is that as a result of the transport and production infrastructures' development of the extraction, processing and transportation of oil and oil products in the conditions of global economic turbulence and the availability of profitable mineral raw materials, domestic demand is restrained by both “inherited” problems and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The study acknowledged the limitations of qualitative research but suggested that the findings could be generalized and further explored in future research endeavors; b. (AL-Saadi et al, 2022)This study delves into the ongoing digital transformation within the oil and gas industry as it navigates the transition toward renewable energy sources.…”
Section: Background Of the Studymentioning
confidence: 98%
“…The study acknowledged the limitations of qualitative research but suggested that the findings could be generalized and further explored in future research endeavors; b. (AL-Saadi et al, 2022)This study delves into the ongoing digital transformation within the oil and gas industry as it navigates the transition toward renewable energy sources.…”
Section: Background Of the Studymentioning
confidence: 98%
“…For the effective management of these processes, a strategic state program is needed to diversify the sectoral structure of the Russian economy, in which clear guidelines for its implementation would be indicated. As rightly noted in [20], "strategic programs are the most important component... of management based on a balanced scorecard, as well as an implementation tool".…”
Section: Factors Of Differential Mining Rent Formationmentioning
confidence: 99%
“…Major international oil companies such as British Petroleum, Shell, Total, and Equinor have long positioned themselves as "integrated energy companies" in an effort to change consumer perceptions of themselves as purely extractive businesses. They are actively investing in the field of renewable energy sources and technologies to integrate them into their own production [4][5][6].…”
Section: Introductionmentioning
confidence: 99%